2022
DOI: 10.1021/acs.analchem.1c04557
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex DNA Walking Machines for Lung Cancer-Associated miRNAs

Abstract: Biomimetic DNA walking machines have gained great success in scrutinizing the microscopic world and sensitive biosensing of disease biomarkers. Despite superb achievements, the research on DNA walking machines for simultaneous detection of multiple analytes is still rare, while the design and realization of multiplexing are considered as an important bottleneck. The multiplex detection of biomarkers can not only improve the specificity of bioassays but also avoid the squander of valuable biological specimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The comparison of the analytical performance of the developed method and other methods for multiplex mRNA/miRNA analysis is shown in Table S5. It can be seen that, compared with the methods based on MS for multiplex miRNA analysis, ,,,, the LODs of the developed method were lower, even lower than those methods involving the amplification technologies of DSNSA, , DNAzyme, and MNAzyme . Compared with the methods based on EDC amplification, , the developed method presented comparable LODs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The comparison of the analytical performance of the developed method and other methods for multiplex mRNA/miRNA analysis is shown in Table S5. It can be seen that, compared with the methods based on MS for multiplex miRNA analysis, ,,,, the LODs of the developed method were lower, even lower than those methods involving the amplification technologies of DSNSA, , DNAzyme, and MNAzyme . Compared with the methods based on EDC amplification, , the developed method presented comparable LODs.…”
Section: Resultsmentioning
confidence: 88%
“…To further improve the sensitivity of the elemental labeling ICP−MS-based multiplex assay for miRNA detection, various signal amplification technologies are introduced, such as duplex-specific nuclease signal amplification (DSNSA), 16 deoxyribozyme (DNAzyme) 26 and multicomponent nucleic acid enzyme (MNAzyme) 27 amplification, and so forth. In our previous work, 27 we designed three MNAzymes that can be assembled with pairs of partzyme A/B in the presence of corresponding three target miRNAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…78 With a similar principle, Wang et al reported ICP-MS based three-dimensional (3D) DNA walking machines to evaluate lung cancer-associated miRNA-125b, miRNA-141 and miRNA-21 in lung cancer cells (A549) and normal cells (HBE), verifying the overexpression of three miRNAs in lung cancer cell lines. 91 Apart from target molecules in biofluids or cell lysates, abnormal expression of disease markers on the cell surface often reflects the pathological status of patients. 92,93 Ma et al designed bifunctional laser cleavable mass probes (LCMPs) to facilitate in situ analysis of multiple glycans, including mannose, sialic acid and N-acetylglucosamine, and to monitor dynamic alterations of glycan expression levels under the stimulation of the respective glycan inhibitor.…”
Section: Mass Spectrometry Detection Of Multiple Biomolecules In Comp...mentioning
confidence: 99%
“…In recent years, inductively coupled plasma mass spectrometry (ICPMS) has achieved remarkable success in the multiplex analysis of biomolecules, owing to the superior multielement analysis capability without spectral interference concomitantly. Advantages like high sensitivity, simple operation, and quick detection offer ICPMS great potential for bioassays. It is currently being used in the assays of nucleic acid, protein, enzyme, small molecules, and single-cell assays. Zhang et al realized dual quantification of multiple DNA assays by means of the rare element labeling strategy . Wang’s group designed a satellite structure constructed from Au NPs and up-conversion nanoparticles (UCNPs), with cancer-associated aptamers as linkers to perform a multiplexed assay of protein on exosomes .…”
Section: Introductionmentioning
confidence: 99%